Design and evaluation of a TEG-PV hybrid energy system for sustainable offshore oil and gas operations using PVsyst simulation - Hilmi, Erik; Yandri, Erkata; Uhanto, Uhanto; Saiful, Rifki; Lodewijk, Dewi Putriani Yogosara; Ariati, Ratna (SINERGI, 2025)
The rising demand for sustainable offshore oil and gas operations has accelerated the need for efficient, low-emission energy systems. Conventional fossil fuel-based systems significantly contribute to greenhouse gas emissions, underscoring the need for innovative alternatives. This study proposes and evaluates a hybrid energy system that integrates thermoelectric generators (TEGs) and photovoltaic (PV) panels to enhance energy efficiency, reduce emissions, and improve the sustainability of offshore operations. The system design utilizes both manual calculations and simulations, employing PVsyst software, to evaluate performance metrics. Results show that the TEG + PV hybrid system improves energy efficiency and reduces carbon emissions by approximately 40% compared to traditional fossil fuel systems. TEGs utilize waste heat from natural gas combustion, while PV panels capture solar energy, creating a synergistic effect that significantly reduces environmental impact. This hybrid configuration also aligns with emission reduction regulations in the oil and gas sector. Beyond environmental benefits, the hybrid system offers economic advantages. Fuel consumption and operational costs are notably reduced, with total savings in capital and operational expenditures (CAPEX and OPEX) reaching IDR 2.53 billion. These savings demonstrate the system’s financial viability and support its adoption in real-world offshore applications. In conclusion, the integration of TEG and PV technologies into a hybrid energy system offers a practical and sustainable solution for offshore oil and gas operations. The system achieves emission reduction targets, enhances operational efficiency, and delivers cost savings, thereby supporting the industry's transition toward more environmentally responsible energy practices.